Motion analysis in sports monitoring techniques: assessment protocols and application to racewalking - Preatoni, E.; La Torre, A.; Santambrogio, G. C.; Rodano, R. (Medicina dello Sport, 2010)
Aim. The aim of this study was to propose guidelines for theproper use of data from motion analysis technologies. The field of investigation concerned the monitoring of individual characteristics in sports movements. The objective was to: determine the number of trials needed to attain stability of individual biomechanical parameters and for a robust description of individual peculiarities; implement a feedback process that could provide coaches and physicians with user-friendly information that might help them in the training or clinical context. Racewalking was chosen as the paradigmatic movement for investigation.